Draft Annual Plan 1972-73 Part II Government of Assam - Planning Commission (Planning Commission, 1972)
The expansion programme of the Cement Factory from 250 tonnes to 850 tonnes per day is in progress. This will improve the economics of the project and will increase supply of Cement in the State. Orders for plant and machinery have been placed with M/S. Utkal Machinery Ltd., M/S. K.C.P. Ltd., Madras, Heavy Electricals Ltd., etc. So far about 80% of the Crushing and screening plant; 50% of the Cement making machineries and 40% of Electrical equipment have been received. the civil construction is going on and it is expected that about 80% of the Civil Engineering works will be completed during the year 1971-72, provided sufficient quantity of steel materials are available.
Planning and Development Department, Government of Assam